2nd Year BA LLB Student, School of Law, Sharda University - Nanda, Bhawna; Jain, Yashasvi (Commonwealth Law Review Journal, 2019)
“In light of the recent outbreak of the #MeToo Movement, various questions regarding the effectiveness of the applicable laws have also erupted. These questions are not just limited to the scope of the existing legal frameworks but, also question the extent to which they are being implemented despite being in force. How relevant is Sexual Harassment at Work Place Act, 2013 when it provides for a limitation period of 03 months only within which a woman can file a complaint? Or how effectively do the Internal Complaint Committees deal with such cases, when they absolutely must? The entire idea of the #MeToo Movement empowers others through empathy which forms a vital process in their own healing journeys. It derives its strength by standing in solidarity. One encourages many. After this motive, should it not be of legislative concern that the mental frame of every woman who has undergone such dreadful experiences cannot be made objectively similar thereby, limiting it to complaining about in a fixed span of time? Well, on the other hand, the fuss and the critics of this movement are plentiful. For a victim woman, while some seek a criminal remedy, depending on the degree of the transgression, or a civil remedy or compensation, or sometimes punitive measures against the harasser by his or her current employer. The paper shall cover the legal arenas which draws attention of the #MeToo Movement. The provisions in relation to The Indian Penal Code, The Code of Criminal Procedure, and Sexual Harassment at Work Place will be discussed in length highlighting both its merits and demerits. The paper will also highlight in brief the nuances of feminism affecting the movement.”